GRUR international : journal of European and international IP law - Drexl, Josef; Hilty, Reto M., 1958-; e ssociated with work. (Oxford : Oxford University Press, 2020)
'GRUR International' is a monthly, peer-reviewed journal which transitions from a German to English-language publication from 2020. The journal deals scientifically with the fields of IP and Competition Law as well as the areas related to them.
"GRUR"--Home page.
Description based on online resource; title from home page (viewed on December 16, 2019).
Keywords: Intellectual property -- Periodicals